Selfish sounds and linguistic evolution : a Darwinian approach to language change - Ritt, Nikolaus, 1960- (Cambridge, 2004)
This book takes an exciting new perspective on language change, by explaining it in terms of Darwin's evolutionary theory. Nikolaus Ritt shows how the constituents of language can be regarded as mental patterns, or 'memes', which copy themselves from one brain to another when communication and language acquisition take place.